The bio-artificial pancreas to treat type 1 diabetes: Perspectives from healthcare professionals in the Netherlands - Dide de Jongh; Eline Bunnik; Behiye Ozcan; Robert Zietse; Emma Massey (Journal of Clinical & Translational Endocrinology)
Aims: Healthcare professionals are relevant stakeholders because of their gatekeeper role in the clinic. This study aims to explore their perspectives on the potential future clinical implementation of the bio-artificial pancreas (BAP) for people with type 1 diabetes, and suitable target groups. Methods: Semi-structured interviews were conducted with 17 healthcare professionals, including endocrinologists, nurses, and pancreas transplant surgeons. Inclusion was stopped once data saturation was reached. The audiotaped interviews were transcribed verbatim. Qualitative content analysis using an inductive approach was conducted to develop themes within a coding framework. Results: Three main themes emerged: (1) hoped-for benefits, which included improved clinical outcomes, enhanced sense of normality, reduced mental burden for patients and their significant others, greater societal participation, and lower costs; (2) concerns, which included safety and effectiveness, inequitable access, accurate information, control over self-management, and organizational challenges; and (3) allocating the BAP during initial implementation, which included prioritizing people who lack effective treatment options, people with mental health issues, and vulnerable people. Conclusions: The results of this study are important for researchers and practitioners involved in the development of the BAP, so that they can align its design and the process of clinical implementation with healthcare professionals’ perspectives.